Fractionated stem cell infusions for patients with plasma cell myeloma undergoing autologous hematopoietic cell transplantation. Issue 8 (2nd August 2016) - Landau, Heather; Wood, Kevin; Chung, David J.; Koehne, Guenther; Lendvai, Nikoletta; Hassoun, Hani; Lesokhin, Alexander; Hoover, Elizabeth; Zheng, Junting; Devlin, Sean M.; Giralt, Sergio
Abstract: We conducted a phase II trial investigating the impact of fractionated hematopoietic cell infusions on engraftment kinetics and symptom burden in patients with plasma cell myeloma (PCM) undergoing autologous hematopoietic cell transplant (AHCT). We hypothesized that multiple hematopoietic cell infusions would reduce duration of neutropenia and enhance immune recovery resulting in a better tolerated procedure. Twenty-six patients received high-dose melphalan followed by multiple cell infusions (Days 0, +2, +4, +6) and were compared to PCM patients ( N = 77) who received high-dose melphalan and a single infusion (Day 0) (concurrent control group). The primary endpoint was number of days with ANC <500K/mcL. Symptom burden was assessed using the MSK-modified MD Anderson Symptom Inventory. Median duration of neutropenia was similar in study (4 days, range 3–5) and control patients (4 days, range 3–9) ( p = 0.654). There was no significant difference in the number of red cell or platelet transfusions, days of fever, diarrhea, antibiotics, number of documented infections, or length of admission. Symptom burden surveys showed that AHCT was well-tolerated in both study and control patients. We conclude that fractionated stem cell infusions following high-dose melphalan do not enhance engraftment kinetics or significantly alter patients' clinical course following AHCT in PCM.